Pattern of Drug Prescription in Patients with Chronic Kidney Disease Maintained on Hemodialysis in a Tertiary Care Hospital (Journal of Nobel Medical College, 2023)
Background: Chronic kidney disease affects the structure and function of the kidneys over a specific period of time. It is a worldwide public health related problem. It is usually associated with increasing age, hypertension, diabetes, cardiovascular disease and lack of exercise.Materials and Methods: It was a cross-sectional observational study conducted at Nobel Medical College Teaching Hospital. A total 150 patients were enrolled in this study from March 2021 to February 2022. Patients aged 18 years and above diagnosed with chronic kidney disease and treated with dialysis were included in this study. Statistical tools were used to describe the relevant data.Results: Chronic kidney disease was more predominant among males 90 (60%) than females 60 (40%). Thecommon co-morbid conditions were hypertension 51(34%) followed by hypertension & diabetes 40 (26.66%). 115 (76.66%) patients were receivinghemodialysis twice followed by 26 (17.33%) who were receiving it thrice a week. An average of 7.03 drugs per prescription was advised. Commonly used drugs were hydrocortisone 145 (96.66%), torsemide 90 (85.71%), and vitamin D3 105 (75%). Among the complications, the most commonly occurred were chills & rigor 15 (10%) followed by backache 12 (8%).Conclusion: Hydrocortisone, torsemide and Vit.D3, were prescribed medications in CKD patients maintained on hemodialysis. Hydrocortisone was commonly used at this tertiary care hospital. Chills & rigor and backache were complication occurred during hemodialysis.